Bond strength of self-etching adhesives applied to different substrates - Kubo, Cinthia S. [UNESP]; Piccioni, Mayra A. R. V. [UNESP]; Tonetto, Mateus R.; Bandeca, Matheus C.; Kuga, Milton C.; Saad, José R. C. [UNESP]; de Andrade, Marcelo F. [UNESP]; de Campos, Edson A. [UNESP] (Jaypee Brothers Medical Publishing, 2017)
Aim: To evaluate the microshear bond strength and adhesive interface using scanning electron microscopy (SEM) of self-etching adhesive systems on normal and artificially hypermineralized dentin substrates. Materials and methods: A total of 65 (n = 65) bovine incisors were divided into two groups according to dentin type: Normal (n = 28) and artificially hypermineralized (n = 29). Composite resin cylinders were placed on these surfaces and cured (3M™ ESPE™ Filtek™ Z350 XT). Each group was divided into four subgroups (n = 7) according to the self-etching adhesive systems used (Clearfil SE Bond, AdheSE®, Adper™ Easy One, and OptiBond™ All-In-One™), and microshear bond tests were performed. In addition, one specimen from each group was prepared for an evaluation of the adhesive interface under a microscope (×2000 magnification). The differences between the groups were determined using two-way analysis of variance (ANOVA) and Tukey’s test (p < 0.05). Results: For normal dentin, the microshear bond strength values in MPa were as follows: Clearfil = 15.65; AdheSE = 14.71; Easy One = 21.92; and OptiBond = 28.43. For hypermineralized dentin, the values were as follows: Clearfil = 20.96; AdheSE = 17.23; and OptiBond = 23.29. There were no significant differences between any of the adhesives used (p > 0.05). When adhesion, dentin, and interaction were treated as factors and analyzed, a significant difference was found only in the case of the adhesive (p = 0.0002). Conclusion: Self-etching adhesive systems with higher degrees of acidity do not necessarily exhibit greater microshear bond strength in hypermineralized teeth. Clinical significance: It is important to obtain bond strength values to analyze the possible clinical performance of the adhesive systems. Furthermore, information on their interactions with different types of dentin substrates proved complementary and useful in the study performed herein.
Keywords: Adhesion; Bond strength; Dental adhesives; Dentin; Scanning electron microscopy